Factors Affecting Investment Decision of Life Insurance Policy - Dinesh Kumar Pant (Journal of Nepalese Management and Research, 2024)
Insurance is a financial service that allows people to save money and insure against risk. It makes sense when the insured wants to guard against a significant economic loss. This study analyzes the factors affecting the decision to invest in life insurance policies in Birendranagar Surkhet, Nepal. The research looked at the relationship between the dependent variable—investment decision—and the independent variables—corporate image, risk and return, tax benefit, claim settlement, and insurance plan. A structured questionnaire based on the judgmental sample approach was used to gather the data, and 195 replies were noted. To evaluate the gathered data, a multivariate regression approach was used. The research indicates that investment choices are mostly influenced by business image, risk and return, insurance plan, and claim settlement; tax advantage has a little impact. The study emphasizes the need for insurance awareness in the study area, highlighting the possible benefits to investors and helping to identify the demographics of the policymakers who are engaged in accelerating the pace of the insurance business.